DESIGN OF PROTECTIVE MASKS AS AN ELEMENT OF MEDICAL CLOTHING: HISTORICAL NOTES AND SYSTEMATIZATION OF CONTEMPORARY TYPES - Кузьменко, Володимир Володимирович; Остапенко, Наталія Валентинівна (Art and Design, 2024)
Purpose: the comprehensive investigation of medical uniforms and their elements, from their historical origins to the classic image of the modern physician, aims to systematize various types of respiratory protective equipment. The study is based on a systematic approach and employs methods of literary-analytical, systemic-structural, and comparative analysis, as well as the historical method. Additional methods include formal, stylistic, and compositional analysis alongside techniques for systematizing visual sources. The study presents a historical review of medical clothing and its components, analyzing the evolution of the form and function of physicians' garments throughout the centuries. It examines and summarizes the range of protective masks available in the Ukrainian consumer market. Artistic, compositional, and structural-technological aspects of mask models were explored and systematized, with visualizations highlighting the shaping features of various mask types. Distinctive characteristics of the products are described in terms of aesthetics and ergonomics, identifying their advantages and limitations. The study provides a detailed analysis and systematization of data on the functional, structural-technological, formative, and compositional features of various types of protective masks. These features include product shaping, fixation methods, frame presence, sealing solutions, material properties, fastening techniques, and the number of material layers. The presented analysis enables consumers to select protective masks that meet quality and operational requirements while establishing correlations between mask parameters considering material properties, aesthetics, and ergonomics, aligned with their protective function. This research contributes to developing an algorithm for implementing integrated design solutions in creating modern protective masks using innovative technologies.